Challenges and Opportunities for Da'wah amidst the Presence of Artificial Intelligence: "ChatGPT" Case Study (Proceeding of Dakwah Saizu International Conference, 2023)
The development of Artificial Intelligence (AI) Technology has experienced rapid progress in recent years. It has increasingly penetrated many aspects of life and cannot be let go, rejected, or shunned in human life. The development of ChatGPT is certainly a challenge and opportunity for Islamic da'wah in the future. This research uses qualitative methods and data collection with literature studies, observation, and documentation. ChatGPT is an AI technology tool that allows humans to access information quickly. It allows Muslims to preach and find information about Islam easily and quickly. ChatGPT is also a challenge for Muslims in preaching because it is narrated, and one answer that must be ascertained first is the validity of the information because it does not have a clear source, unlike Google, which has many alternatives and users can choose which one to click and clearer the source. The challenge for Muslims in preaching amid the presence of AI Technology is producing as much valid information as possible, which AI can apply.